Patient-reported outcomes measures of X-linked hypophosphataemia participants: findings from a prospective cohort study in the UK - Cole, S; Sanchez-Santos, MT; Kolovos, S; Javaid, MK; Pinedo-Villanueva, R (BioMed Central, 2023)
Background X-linked hypophosphataemia (XLH) is a rare genetic condition passed on through the X chromosome which causes multiple symptoms including weakened teeth, bones, and muscles. Due to the rarity of the condition, little is known about the health outcomes as reported by people with the disease. The objectives of this study were threefold: to characterise key patient reported outcome measures (PROMs) in adults with XLH, to identify clusters of symptom-severity groups based on PROMs, and to analyse the longitudinal progression of available PROMs.